Datum Verification for Coastal Engineering Studies - Hazmi Hamdan; Mustaffa Anjang Ahmad; Kahlid, Muhammad Dzikri; Radzuan Bin Sa'ari; Mokhamad Nur Cahyadi (International Journal of Sustainable Construction Engineering and Technology, 2024)
This research paper focuses on verifying the vertical datum for coastal engineering studies at Batu Pahat, Johor, using Global Navigation Satellite System (GNSS) technology. The study aimed to address potential impacts from climate change, sea level rise, and tectonic movements on existing coastal structures such as stone revetments and long stretches of embankments or bounds along the coastline can prevent sea water from entering the drain, which can cause property damage and crop and plant destruction.  Levelling work was conducted to establish accurate height measurements relative to a datum, ensuring precise readings from tide gauges. The research involved two key locations along the Batu Pahat shoreline, employing digital levelling techniques for data collection. The Mean Sea Level (MSL) value above Chart Datum (CD) at Kuala Batu Pahat was determined to be 1.59 m, with a slight variation observed along the shore while considering the most recent 1-year CD observation, which was established in 1979 by the National Hydrographic Center of the Royal Malaysian Navy. The success of the project was attributed to the acceptable differences between observed values, confirming the reliability of the established Land Survey Datum. Overall, this study underscores the importance of datum verification in coastal engineering applications to mitigate potential risks and ensure accurate measurements for future development projects.